O projeto poético de Ângela lago: redes da criação - Camerlingo, Tamires Henrique Lacerda (2020)
This work has as its central theme to study the poetic project of Ângela Lago. In particular, it aims to examine this theme in the translation arrangements made from the interaction between word and image. The problem proposed for this research is how language connections are made in picture books? What is the way the author develops to unite tradition and modernity? With this specification of the problem, the hypothesis to be tested is that Lago's stories are constantly constructed in an attempt to rescue customs, cultures, and values to disseminate them in today's society. Thus, the author could find in the use of graphic, textual and visual resources an innovative way to refunctualize the set of elements of narrative composition. The object of study of this research, the author Ângela Lago, has been recognized in recent decades for her numerous artistic productions. His works are marked by traces and fragments of countless stories of yore that are taken up in contemporary times. The worlds of yesterday, today, and tomorrow mingle in their paintings and verses to create new realities and meanings. The purpose of this research is to understand from the concepts of semiosis how Angela Lago creates a peculiar way of rescuing stories from the past. For this purpose, the theories of philosophers Octavio Paz (2012) and Antoine Compagnon (2010) and theorists and critics Cecilia Salles (2015) Sophie Van der Linden (2011). Allocated in the Research Line: Creation processes in communication and culture, this thesis aims to show the importance of semiotic analysis of Ângela Lago's poetic creation project